Vision based control of a mobile robot - Zhang, Xiao (2014)
Vision-Based Robotic control is a revolutionary technology for new generation automation control. It uses the feedback information from the vision sensor to control the motion of a robot. The vision sensor used in the control system enables the robot with the ‘seeing’ ability to understand the unknown environment, which extend the range of usages for robots. Here in this project the Turtlebot2 is used as the mobile robot system with a Kinect camera attached on. The objective is to control the Turtlebot2 for certain motion perforce based by the vision information. Vision based tracking is one of the application which is implemented in the first part of this project. The OpenTLD is used for object tracking in a real-time video steam. Combine the TLD with a P controller, the